The role of foreign donors in rebuilding the Ukrainian nation-state. Issue 1 (2nd January 2018) - Oleinik, Anton
ABSTRACT: The viewpoint discusses the role of foreign donors in rebuilding the Ukrainian nation-state. It argues that a gardener's care is needed – not guidance, traditional teaching, or direction, but assistance. Foreign donors' activities should be oriented principally to the support of internal points of growth, social and economic. The task of empowering actors that show promise to propel socio-economic development from within can and should be prioritised. The policies of empowering local actors (as opposed to financing the government and established businesses) involve first and foremost supporting bottom-up initiatives and start-ups that have demonstrated their relevance and promise.